Modern rhythmic notation - Read, Gardner (Indiana Indiana University Press, 1987)
Twentieth-century music has significantly advanced the role of rhythm. The many variants of rhythmic notation, standard and experimental alike, encountered in contemporary music frequently demand explanation and interpretation. This book catalogs and clarifies the numerous ways of notating syncopation and alternative standard rhythmic figures, new time signatures, irrational rhythmic groupings within regular and irregular meters, experimental metrical concepts and techniques, analogs, and, finally, polymeters. Read compares traditional and present-day methods of delineating the same musical expressions, from fairly simple combinations to extremely complicated patterns.Show More Show Less